Administration of mRNA-Nanomedicine-Augmented Calvarial Defect Healing via Endochondral Ossification - Hsi-Kai Tsou; Cheng-Hsin Wu; Long Yi Chan; Kazunori Kataoka; Nanae Itokazu; Minoru Tsuzuki; Hsuan Hu; Guan-Yu Zhuo; Keiji Itaka; Chin-Yu Lin (MDPI AG, 2023)
Large-area craniofacial defects remain a challenge for orthopaedists, hastening the need to develop a facile and safe tissue engineering strategy; osteoconductive material and a combination of optimal growth factors and microenvironment should be considered. Faced with the unmet need, we propose that abundant cytokines and chemokines can be secreted from the bone defect, provoking the infiltration of endogenous stem cells to assist bone regeneration. We can provide a potent mRNA medicine cocktail to promptly initiate the formation of bone templates, osteogenesis, and subsequent bone matrix deposition via endochondral ossification, which may retard rapid fibroblast infiltration and prevent the formation of atrophic non-union. We explored the mutual interaction of BMP2 and TGFβ3 mRNA, both potent chondrogenic factors, on inducing endochondral ossification; examined the influence of in vitro the transcribed polyA tail length on mRNA stability; prepared mRNA nanomedicine using a PEGylated polyaspartamide block copolymer loaded in a gelatin sponge and grafted in a critical-sized calvarial defect; and evaluated bone regeneration using histological and μCT examination. The BMP2 and TGFβ3 composite mRNA nanomedicine resulted in over 10-fold new bone volume (BV) regeneration in 8 weeks than the BMP2 mRNA nanomedicine administration alone, demonstrating that the TGFβ3 mRNA nanomedicine synergistically enhances the bone's formation capability, which is induced by BMP2 mRNA nanomedicine. Our data demonstrated that mRNA-medicine-mediated endochondral ossification provides an alternative cell-free tissue engineering methodology for guiding craniofacial defect healing.